2008
DOI: 10.1108/13552510810861950
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating the cost of quality in supply chain design

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 20 publications
2
41
0
Order By: Relevance
“…Such models are of large scale and require strong computational power [38]. The first work concerning SCND was developed by Geoffrion and Graves [39] that presented a SCND for optimizing the flow of finished products from plants to distribution centers.…”
Section: Incorporating Coq In Scndmentioning
confidence: 99%
See 1 more Smart Citation
“…Such models are of large scale and require strong computational power [38]. The first work concerning SCND was developed by Geoffrion and Graves [39] that presented a SCND for optimizing the flow of finished products from plants to distribution centers.…”
Section: Incorporating Coq In Scndmentioning
confidence: 99%
“…Srivastava [4] measures CoQ in monetary terms using PAF model. Ramudhin et al [38] also introduced a model integrating the Cost of Quality (CoQ) into the supply chain network and found that incorporating COQ in supply chain network design will ensure the lowest overall cost, and reduce the probability of defects of approximately 16%. Castillo-Villar et al [10] developed a mathematical model incorporating CoQ in Supply Chain Network (SCN).…”
Section: Incorporating Coq In Scndmentioning
confidence: 99%
“…More papers investigate the effect of price and quality on demand, and others how demand changes by variation of price, quality, brand diversity, and location of factory come about [7,28,10,17,22,26,12,15,27,11,9,42,35]. Finally there are papers that incorporate quality in designing supply chain networks [13,1,41,30].…”
Section: Introductionmentioning
confidence: 99%
“…They estimated quality costs in monetary terms according to P-A-F model and used standard DMAIC (Define-Measure-Analyze-Improve-Control) methodology for analysis at selected third-party contract manufacturing sites of a pharmaceutical company. Ramudhin et al (2008) also focused on integration of quality cost in the supply chain. Their study presented a mathematical model for a single product, three-echelon system (i.e.…”
Section: Quality Cost In Supply Chainmentioning
confidence: 99%
“…Some studies, e.g. Ramudhin et al (2008), focused on total quality cost at suppliers and suggested adding the quality cost of manufacturers (plants) in their model for further research. On the other hand, some studies investigated the revenue sharing in supply chain management, for example, Govindan & Popiuc (2014) shows that significant returns are realized for all supply chain partners in revenue sharing cases, and the performance improves through coordination with revenue sharing contracts.…”
Section: Introductionmentioning
confidence: 99%